Knowledge, Attitude, and Practice towards Needle Stick Injury among Nursing Students of Saida Waheed FMH College of Nursing, Lahore - Zohaib, Muhammad; Rehman, Nosheen; Saba, Sehrash; Nawaz, Aqsa; Zafer, Sinha; Asif, Mona; Siddique, Muhammad Abu Bakar; Arshad, Hina (Biological and Clinical Sciences Research Journal, 2025)
Needle stick injuries (NSIs) pose a serious occupational hazard for healthcare workers, including nursing students during clinical training. Despite having basic knowledge, the translation of this knowledge into safe practices remains inconsistent in many low-resource settings. Objective: To assess the knowledge, attitudes, and practices (KAP) of nursing students regarding NSIs in a tertiary care educational setting in Pakistan. Methods: A descriptive cross-sectional study was conducted among 128 nursing students at a tertiary care institute in Lahore. Data were collected using a structured, self-administered questionnaire divided into three sections: knowledge, attitude, and practice. Descriptive statistics were calculated using SPSS version 25, and results were presented in frequency tables. Results: Most students demonstrated good knowledge regarding NSI risks and prevention (e.g., 98.4% recognized proper disposal of needles; 87.7% acknowledged the need for immediate reporting). Positive attitudes were observed toward NSI prevention (95.3% supported the use of PPE; 89.4% agreed NSIs must be reported). However, poor practices were evident—46.9% always recapped used needles, and only 45.3% reported NSIs promptly. Furthermore, only 28.9% had received formal training on NSI prevention. Conclusion: Despite high knowledge and positive attitudes, unsafe practices such as needle recapping and poor reporting highlight the need for improved clinical training and enforcement of standard safety protocols. Regular workshops and simulation-based learning should be integrated into nursing curricula to enhance compliance with NSI prevention guidelines.